ChemInform Abstract: Ecological Recycling of a Bio‐Based Catalyst for Cu Click Reaction: A New Strategy for a Greener Sustainable Catalysis. Issue 39 (September 2016) - Clave, G.; Garoux, L.; Boulanger, C.; Hesemann, P.; Grison, C.
Abstract: The Cu‐based ecocatalyst produced via rhizofiltration of copper‐rich effluents using E.